2019
DOI: 10.3390/ijms20174176
|View full text |Cite
|
Sign up to set email alerts
|

FOXG1-Related Syndrome: From Clinical to Molecular Genetics and Pathogenic Mechanisms

Abstract: Individuals with mutations in forkhead box G1 (FOXG1) belong to a distinct clinical entity, termed “FOXG1-related encephalopathy”. There are two clinical phenotypes/syndromes identified in FOXG1-related encephalopathy, duplications and deletions/intragenic mutations. In children with deletions or intragenic mutations of FOXG1, the recognized clinical features include microcephaly, developmental delay, severe cognitive disabilities, early-onset dyskinesia and hyperkinetic movements, stereotypies, epilepsy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 99 publications
0
75
0
Order By: Relevance
“…The N-terminus residues of FOXG1 are highly variable and constrained to be disordered, while the residues from FBD to the C-terminus are constrained and contain an ordered structure. It has been reported that mutations in the N-terminal are more likely to be associated with severe phenotypes, and mutations in the C-terminal are associated with milder phenotypes [52]. We reported and predicted a phosphorylation site located in Ser 19 to be conserved in chordates even though it is located among flexible disordered regions; casein kinase 1 (CK1) modifies this site and promotes nuclear import of FOXG1, which corresponds to neurogenesis in the forebrain [67].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The N-terminus residues of FOXG1 are highly variable and constrained to be disordered, while the residues from FBD to the C-terminus are constrained and contain an ordered structure. It has been reported that mutations in the N-terminal are more likely to be associated with severe phenotypes, and mutations in the C-terminal are associated with milder phenotypes [52]. We reported and predicted a phosphorylation site located in Ser 19 to be conserved in chordates even though it is located among flexible disordered regions; casein kinase 1 (CK1) modifies this site and promotes nuclear import of FOXG1, which corresponds to neurogenesis in the forebrain [67].…”
Section: Discussionmentioning
confidence: 98%
“…RTT itself has attracted considerable attention as its causative protein displayed features related to epigenetics and were shown to have partially or fully disordered structures. [15,52]. The co-repressor complex itself denotes a conserved mechanism that manifests in diverse forms and may have several functional entities depending on the context in which they are recruited [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, all three proteins were shown to have multiple binding partners, and FOXG1 and MeCP2 displayed the highest number of partners, some of which were evolutionarily acquired before the metazoan evolved. By cooperating with various proteins partners, particularly the co-repressor complex, FOXG1 or MeCP2 can modulate the expression and suppression of different genes [15,52]. The co-repressor complex itself denotes a conserved mechanism that manifests in diverse forms and may have several functional entities depending on the context in which they are recruited [53].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the necessity to regulate either FOXG1 or MeCP2 concentration precisely; otherwise, altered availability is likely to be deleterious. Several studies have shown that either overexpression or under-expression of MeCP2 and FOXG1 corresponds to neurological deficits; this phenomenon may not independent from their co-repressor complex that has been showed to play roles in neurogenesis and neuron maturation for FOXG1, and MeCP2, respectively [7,15,52]. On the other hand, CDKL5 binds to a fewer number of proteins that have functions in regulating cell adhesion, ciliogenesis, and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%